2016
DOI: 10.4338/aci-2016-01-ra-0003
|View full text |Cite
|
Sign up to set email alerts
|

Patient Portals

Abstract: The vast majority of patients who were given an access code for My UNC Chart did not use it within 30 days of discharge. Of those who used the portal, active users had a higher odds of being readmitted within 30 days. Health care systems should consider strategies to: (1) increase overall use of patient portals and (2) target patients with the highest comorbidity scores to reduce hospital readmissions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(71 citation statements)
references
References 24 publications
4
67
0
Order By: Relevance
“…EHR patient portals represent an option to increase patient access to their medical information, providing an alternative to slower or more labor-intensive methods such as regular mail, in-person visits, or telephone calls. [ 7 8 9 10 11 12 13 14 15 16 17 ] Access to diagnostic test results is one of the most popular features of EHR patient portals. [ 18 20 ] Understanding patterns of EHR patient portal use can be helpful to healthcare providers, hospital administrators, information technology personnel, and patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EHR patient portals represent an option to increase patient access to their medical information, providing an alternative to slower or more labor-intensive methods such as regular mail, in-person visits, or telephone calls. [ 7 8 9 10 11 12 13 14 15 16 17 ] Access to diagnostic test results is one of the most popular features of EHR patient portals. [ 18 20 ] Understanding patterns of EHR patient portal use can be helpful to healthcare providers, hospital administrators, information technology personnel, and patients.…”
Section: Discussionmentioning
confidence: 99%
“…[ 10 11 ] Depending on institutional policies, patient portals can allow patients access to a wide variety of personal health information such as clinical notes, laboratory results, radiology reports, immunization records, and medication history. [ 8 12 13 14 15 16 17 ]…”
Section: Introductionmentioning
confidence: 99%
“…Type of practice's marketing strategies 1 128 1 promotional materials or clinicians Hospital location 1 86 1 Adoption rate of EHRs by the organisation 1 115 1…”
Section: Human-technology Interaction Factorsmentioning
confidence: 99%
“…Fewer than one-third of patients report having logged into their patient portal accounts in the past year [ 18 , 19 ]. Similar to analyses of electronic health records (EHRs), these primary surveys found that measures related to health disparities, including lower educational attainment, older age, minority group membership, and living in rural communities were associated with lower patient portal utilization [ 16 , 19 ]. Furthermore, Peacock and colleagues [ 18 ] found that health care providers were less likely to offer patient portal access to minority patients than white patients.…”
Section: Introductionmentioning
confidence: 99%